RESPUESTA HEMATOLÓGICA EN PREADULTOS DE LANGOSTA DE AGUA DULCE (Cherax quadricarinatus) CON INCLUSIÓN DE HARINA DE Lemna minor EN DIETA - Muñoz Vinces, Kenlly Nathalie (2023)
The research was carried out at the “La María” Campus, belonging to the State Technical University of Quevedo, in the aquaculture laboratory, for which 6 treatments with three repetitions were used in a DCA. Each of the treatments was structured with an experimental diet with different percentages of Lemna minor flour (0 – control, 4, 8, 12, 16 and 20%). The main objective of this research was the evaluation of the hematological response in pre-adult freshwater lobster (Cherax quadricarinatus) with the inclusion of Lemna minor flour. For this reason, the results were expressed as follows, regarding the survival variable due to hypoxia in all treatments they responded with 100% survival.